Serotonin syndrome following left ventricular assist device implantation: A report and institution-specific strategy for prevention. Issue 6 (December 2019) - Katzianer, David; Chism, Keira; Qureshi, Ataul M.; Watson, Ryan; Massey, Howard Todd; Boyle, Andrew J.; Reeves, Gordon; Danelich, Ilya
Abstract: Serotonin syndrome is a potentially lethal complication of antidepressant therapy. Cardiac surgical patients are at particularly high risk of serotonin syndrome due to the prevalence of depression in patients with advanced cardiac disease, many of whom receive multiple serotonergic agents in the perioperative period. Here, we describe a case of postoperative serotonin syndrome following methylene blue administration for perioperative vasoplegia during left ventricular assist device implantation. We additionally describe an institution-specific strategy to minimize future occurrences of serotonin syndrome in this high-risk population. <Learning objective: Antidepressant medication use is prevalent in advanced heart failure patients. With serotonergic antidepressants, perioperative drug interactions may potentiate serious adverse drug events such as serotonin syndrome. In this report, we describe a case of serotonin syndrome following treatment of perioperative vasoplegia with methylene blue and describe steps our institution has implemented to prevent future occurrences.>